2018
DOI: 10.23865/jased.v4.1197
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ perceived cost of attending physical education

Abstract: Objective: The purpose of this study was to examine the effect of flipped learning (FL) on adolescents’ motivation to participate in physical education (PE) lessons in secondary and upper secondary schools based on adolescents’ perceived costs of attending PE. Methods: The students (N=338; 45.3% girls) were recruited from six secondary and upper secondary schools from three different counties in Norway during the spring of 2016. The data were collected using open-ended questions. Results: The data analysis rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Casey et al [70] argue that there is a lack of research on how digital technologies are used and how they affect motivation and learning in PE. However, there are studies suggesting that FL has a positive impact on student motivation in secondary school PE [71], especially among girls [72,73], and that both cognitive learning and perceived value of the subject are positively affected when a FL framework is applied in PE [67]. In a Chinese study of teaching basketball in PE, Chiang et al [74] concluded that female students benefit more from flipped learning strategies compared to boys.…”
Section: Flipped Learningmentioning
confidence: 99%
“…Casey et al [70] argue that there is a lack of research on how digital technologies are used and how they affect motivation and learning in PE. However, there are studies suggesting that FL has a positive impact on student motivation in secondary school PE [71], especially among girls [72,73], and that both cognitive learning and perceived value of the subject are positively affected when a FL framework is applied in PE [67]. In a Chinese study of teaching basketball in PE, Chiang et al [74] concluded that female students benefit more from flipped learning strategies compared to boys.…”
Section: Flipped Learningmentioning
confidence: 99%
“…There was greater motivation towards the participation and practice of PE using the FL approach, according to the research carried out by Østerlie and Kjelaas (2019) in a secondary school setting. Further, when female secondary school PE students were attending an FL learning environment, studies reported higher expectancy beliefs and attainment values (Østerlie, 2018b), and lower perceived costs of attending PE (Østerlie, 2018a). In a situational motivation context, Østerlie and Mehus (2020) found, when changing the nature of the PE content to be more play-like, a negative motivational change for male secondary students unless the activity changes were placed within an explanatory rationale through FL.…”
Section: Summarising Reporting and Discussion Of Findingsmentioning
confidence: 99%
“…Expert literature in this field of knowledge reflects how the application of FL reports a learning benefit made by students [19]. Recent research analyzed various academic indicators and verified how the application of FL contributes to improving the indexes of both academic (content deepening, class time, and ratings) and psychosocial variables (motivation, student-content-teacher interactions, autonomy, collaboration, and problem solving) with respect to the implementation of other methodologies, such as the traditional one of an expository nature [5,14,[16][17][18][19][20][30][31][32][33][34][35][36][37][38][39][40][41][42][61][62][63][64][65][66][67][68][69][70][71][72][73]76].…”
Section: Discussionmentioning
confidence: 99%
“…After analyzing various recent impact studies that carried out training practices and experiences using FL in different subjects and educational levels, it was verified that they all follow the same methodological pattern, that is, the application of this approach mostly uses a similar instructional procedure [63][64][65][66][67][68]. The processes are synthesized in the previous visualization of videos outside the school environment, followed by the carrying out of practical activities in the educational center, then ending with a reinforcement again in digital media to solve doubts that have arisen and to visualize new audiovisual content of the next sessions formative [21][22][23][24][25].…”
Section: Justification and Objectivesmentioning
confidence: 99%
See 1 more Smart Citation